The process of acquisition and development of handwriting - Capellini, Simone Aparecida [UNESP]; Cardoso, Monique Herrera [UNESP] (My University, 2018)
This chapter initially addresses the definition and function of writing, its relation to oral language and other skills necessary for its development, focusing on the requirements of the Brazilian Ministry of Education and the practices used by educational institutions. It also discusses the concept of dysgraphia and the characteristics of this diagnosis, given the importance of readability and speed of writing, besides characterizing the possible pathologies that may present this spectrum of dysgraphia. In addition, it presents a survey of studies and international instruments, which investigate the quality, and speed of handwriting, reinforcing the shortage of articles in Brazil, and it is concluded with important aspects to be taken into account during handwriting evaluation. It is expected that this chapter may help health and education professionals to elucidate how the process of acquiring and developing handwriting occurs, emphasizing its importance nowadays.
Keywords: Dysgraphia; Education; Manual writing